FORMULASI SABUN TRANSPARAN MINYAK BUAH MERAH (Pandanus conoideus Lam.) - Audia Triani Olii; Aztriana Aztriana; Nursiah Hasyim (As-Syifaa Jurnal Farmasi, 2015)
Red fruit oil is known to be very useful as antioxidants are beneficial for skin health, especially to prevent damage cell components that cause premature aging of the skin. Based on the study of antioxidant activity with IC50 value of 53.47 µg / mL. This study aimed to obtain a formula that possess optimal physical stability. In this study, three formulas designed by varying the precursor, namely the formula I with soap formation ingredients palm oil and olive oil, the formula II with VCO soap-forming ingredients and olive oil, and formula III with ingredients forming castor oil soaps and oils olives. Each physical stability of the formulations was evaluated by testing parameters include the foam test, hardness test, test the pH, organoleptic and sensory evaluation test on the skin. Results showed that the formula that has optimum physical stability is Formula I with component-forming material palm oil soaps and olive oil.